Iodide n,π-chelate complexes of platinum(II) based on N-allyl substituted thioureas and their effect on the activity of hepatobiliary system enzymes in comparison with chloride analogs - V. Orysyk; L. Garmanchuk; S. Orysyk; Yu. Zborovskii; S. Shishkina; I. Stupak; P. Novikova; D. Ostapchenko; N. Khranovska; V. Pekhnyo; M. Vovk (The Ukrainian Biochemical Journal)
The search for new effective drugs in the treatment of neoplasm remains relevant even today, since the adaptation of transformed cells to the action of classical drugs contributes to the emergence of drug resistance. This applies to a number of classic chemotherapy drugs of the platinum series, in particular cisplatin. In this work, we describe the effect of novel analogs of cisplatin on HepG2 cells and on the key enzyme of antioxidant protection system gammaglutamyltranspeptidase, which plays an important role in the acquisition of drug resistance to anticancer drugs by tumor cells. New mononuclear iodide n,π-chelate complexes of Pt(II) with substituted thioureas N-allylmorpholine-4-carbothioamide or 3-allyl-1,1-diethylthiourea were obtained as analogs of cisplatin. All compounds were investigated by UV-Vis, IR, and 1H/13С NMR spectra. Complex I was described by single-crystal X-ray diffraction study. Also, the effect of these analogs on alanine aminotransferase, aspartate aminotransferase, lactate dehydrogenase, which are marker enzymes of liver cells, release of which into the blood indicates liver pathologies, was investigated. All studies were carried out in comparison with chloride n,π-chelate complexes of platinum obtained earlier (however, the effect of these chloride analogs of platinum on enzymes of the hepatobiliary system was investigated for the first time in this work). The results have shown that the studied compounds are better cytostatics/cytotoxics than cisplatin both according to IC50 and apoptosis level of HepG2 cells. It is established that, for the most part, effect of the studied complexes is reduced to a decrease in the degree of malignancy of cells of hepatocyte lines and the activity of LDH and GHT, as well as a decrease in consumed glucose.